Prevención y Complicaciones de la Fiebre Reumática. Hospital Instituto Ecuatoriano de Seguridad Social. Riobamba, 2020-2021 - Johanna Gabriela, Guamán Andrade (2021)
ABSTRACT Objective: To identify main complications of rheumatic fever and its prevention in patients treated at the Hospital General IESS Riobamba during the period 2020 – 2021. Population and sample: The study population was 182 patients with rheumatic fever, but 125 complied with the inclusion criteria. Method: This was a descriptive, non-experimental, correlational, retrospective and cross-sectional study. For data collection, medical records registered in the AS400 system were used. Results: Of the total of participants, 88.5% were female, higher education (45.6%), urban residence (59.9%). The most frequent sign was arthritis in 84.6%, while rheumatic heart disease was the most evident complication in 25.6% of the population. Mitral stenosis was the most observed echocardiographic finding (83.9%). In the bivarial analysis, there is a relationship between recurrent rheumatic fever and the development of complications (chi2: 14,75, p: 0.0001 PR = 2.72; 95% CI: 2.46 - 7.57). Conclusion: The main complication of rheumatic fever was heart disease, which is related to the recurrence of the pathology. It is necessary to strengthen primary prevention measures at the local level. Key words: Rheumatic fever, Group A streptococcal infections, Prevention, Complications. (DeCS) Reviewed by: Lic. Dario Javier Cutiopala León ENGLISH PROFESSOR c.c. 0604581066